2003
DOI: 10.1177/095400830301500106
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Aging of Twaron Fibers

Abstract: The residual effects of thermal aging on Twaron fibers have been studied using X-ray diffraction, weight analysis, scanning electron microscopy and tensile testing. X-ray data from isothermally aged fibers indicate the introduction of changes at the level of the crystal lattice, which include reduction in crystallinity, variations in 20 values, half width and azimuthal spread of reflections. Isothermal aging also introduces weight loss. Examination of the surface of fibers has shown that damages in the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
5
13
0
1
Order By: Relevance
“…Figure 3 shows the crystallite shape in Twaron fibers at different temperatures; small changes in the shapes occur only at the periphery of these crystallites, which brings out the essence of our results. This implies that these small changes in crystallites of Twaron fibers is due to the breaking of inter‐ and intra‐ weak hydrogen bonds like CH… O; NH… O, and OH… O. Scanning electron microscope studies of thermally treated Twaron fibers reported earlier do support the results observed here 24. In fact, it is observed that there are very few regions on the surface of the fiber with localized pits, sponge‐like and wool‐like appearances when exposed to different temperatures, which are indicative of small surface changes, and the presence of these regions slightly alters the size of crystallite regions.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 3 shows the crystallite shape in Twaron fibers at different temperatures; small changes in the shapes occur only at the periphery of these crystallites, which brings out the essence of our results. This implies that these small changes in crystallites of Twaron fibers is due to the breaking of inter‐ and intra‐ weak hydrogen bonds like CH… O; NH… O, and OH… O. Scanning electron microscope studies of thermally treated Twaron fibers reported earlier do support the results observed here 24. In fact, it is observed that there are very few regions on the surface of the fiber with localized pits, sponge‐like and wool‐like appearances when exposed to different temperatures, which are indicative of small surface changes, and the presence of these regions slightly alters the size of crystallite regions.…”
Section: Resultssupporting
confidence: 89%
“…The computed microcrystalline parameters like crystalline size (number of unit cells) 〈 N 〉, lattice strain ( g in %), the width of the crystalline size distribution α, and the goodness of the fit are given in Table I. We have also reproduced the ratio S ( T )/ S ( O ), with S ( T ) as the tenacity at temperature T and S ( O ) as the tenacity at room temperature 24. The goodness of fit while computing these tenacity parameters is less than 5%, for all the temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…At this juncture, it must be pointed out that the overall nature of the changes introduced in the X-ray diffraction patterns from thermally aged PTFE viz., shifts in the 2y values, changes in the intensities, half width, etc., are similar to those found in the polyamides mentioned earlier [4][5][6][7][8][9][10][11][12][13]. On the basis of the similarities, it may be surmised that the residual effect of thermal aging on the crystal structural characteristics is not exclusive to polyamides.…”
Section: Half Widthsupporting
confidence: 84%
“…In the past, the authors have carried out extensive investigations on the effects of thermal aging on some polyamides viz., Kevlar, Twaron, Nylon 6,6, and Nomex. Their studies established that the thermal aging causes significant residual effects on the crystal as well as macrostructural characteristics, tensile properties, weight, etc., of the polyamides [4][5][6][7][8][9][10][11][12][13]. This article reports the details of observations on the residual effects of thermal aging on the crystal structural characteristics of an entirely different type of polymer viz., a fluoro carbon, poly(tetra fluoro ethylene) (PTFE), derived by wide angle X-ray diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Cette diminution de la résistance mécanique peut être attribuée à une augmentation de la taille apparente latérale des cristallites (Rao et al, 2001a ;Rao et al, 2001b) et/ou à des dégradations surfaciques (Dobb et al, 1990 ;Jain et al, 2003). De même, après un an de vieillissement à « pH9, 80 °C », la résistance mécanique passe de 3,21 ± 0,35 GPa à 2,91 ± 0,17 GPa, soit une diminution d'environ 9 %.…”
Section: Analyses Fonctionnellesunclassified